A review of blood usage and wastage in a tertiary heart center. Issue 2 (3rd March 2020) - Shamshirian, Amir; Mohseni, Ali Reza; Pourfathollah, Ali Akbar; Mehdipour, Shirin; Hosseini, Samira; Ghorbanpour, Atiyeh; Azizi, Soheil
ABSTRACT: Background/Objectives : Blood is a vital resource that its utilization is ever increasing throughout the world and blood wastage is a global challenge that needs to be controlled. Most blood resources are used during complications of pregnancy, trauma, severe childhood anemia, gynecology, cancers, surgery, hematology disorders, and chronic diseases. Units that are expired, broken bags, returning the blood unit after 30 min, blood clotted units, etc., which are due to lack of awareness may result in the wastage of blood products. The objective of this study is to analyze the usage and wastage of blood and its products in Mazandaran heart center. Methods : In this retrospective study, the survey was carried out on the data that were obtained from Mazandaran heart center of Sari, Iran during 2012–2017. Data included details of usage and wastage on blood and its product units. MS Excel 2016 and SPSS 16.0 were used in analysis and diagrams. Results : A total of 35, 686 blood units were consumed, which included 55.7% packed red blood cells (PRBCs), 33.9% platelets (Plts), 8.9% fresh-frozen-plasma (FFP), and 8.9% cryoprecipitates. Moreover, 823 blood units including 41.4% FFP, 37.2% PRBCs, and 21.4% Plts were wasted mostly because of inappropriate order (70.6%). Cross-match to transfusion ratio was 1.13. The intensive care unit reported the highest level of blood intake by 45.0%. The blood group O+ was the most frequent by 34.8%. In addition, blood wastage has decreased over study period by approximately 10.0%. Conclusion : Our study showed not only the increasing pattern of blood usage but also the dropping pattern of blood wastage due to hemovigilance performance and additional training in our healthcare center. We found that the main reason for the blood wastage in this center is an excessive order of blood units.